Peningkatan ketahanan keluarga melalui psikoedukasi komunikasi asertif di KSM Migunani Dukuh, Sinduharjo, Ngaglik, Sleman, Yogyakarta (Universitas Islam Indonesia, 2026)
Family resilience is a crucial aspect in maintaining harmony, psychological well-being, and the ability to cope with life’s challenges. In the KSM “Migunani” in Sleman, limited communication skills among family members were identified, which may lead to misunderstandings and hinder joint decision-making. This community service program aims to enhance family resilience by strengthening communication skills, particularly assertive communication. The method used was psychoeducation delivered to KSM members, especially mothers. The results showed a significant improvement in participants’ assertive communication skills (t = -5.17; p < 0.001). The program also increased participants’ awareness of the importance of effective communication in building harmonious and resilient families. Overall, this initiative had a positive impact on both individual and community capacity in strengthening family resilience. Therefore, sustained collaboration among academics, communities, and local stakeholders is essential to support the development of resilient families as a foundation for social resilience.